2001
DOI: 10.1186/cc1276
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in children with septic shock

Abstract: P14 Facial continuous positive airway pressure therapy for cardiogenic pulmonary oedema: a study of its efficacy in an emergency department setting within the UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Mg deficiency was linked to inborn error of metabolism in our study. 16 De Menezes et al reported 76% of the critical children had hypophosphatemia on admission 6 & 60% in a retrospective Turkish study. 19 Meneses et al found that hypophosphatemia was common in the first 10 days of ICU hospitalization and was associated with the diagnosis of respiratory disease, use of dopamine, and malnutrition.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mg deficiency was linked to inborn error of metabolism in our study. 16 De Menezes et al reported 76% of the critical children had hypophosphatemia on admission 6 & 60% in a retrospective Turkish study. 19 Meneses et al found that hypophosphatemia was common in the first 10 days of ICU hospitalization and was associated with the diagnosis of respiratory disease, use of dopamine, and malnutrition.…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Buysse CMP et al on 26 children with septic shock they found that 68% were hypocalcaemic. 16 Haghbin et al mentioned that the prevalence of hyperglycemia and hypocalcaemia in critically ill patients is considerable with no link to ventilation. 12 Table 4 Comparison between hypocalcemia and normocalcemia on admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study (68%) were hypocalcemic (19 survivors and 7 non-survivors). 27 Clinical suspicion is very important for identification of electrolyte imbalance in these patients. :Electrolyte imbalances are common in children with different types of infections, especially in diarrhea with specific symptoms of electrolyte abnormality often merged with the underlying disease.…”
Section: Fig 5 : Different Level Of Hyponatremiamentioning
confidence: 99%